Dynamic response reanalysis for modified structures under arbitrary excitation using epsilon-algorithm - Chen, Su Huan; Ma, Liang; Meng, Guangwei (Computers & structures, 2008)
Using the Neumann series and epsilon-algorithm, a new dynamic response reanalysis method for modified structures under arbitrary excitation is developed. Based on the Newmark method, the approximate displacement responses in each time step can be obtained by using the epsilon-algorithm. The basis vectors obtained by the Neumann series expansion can be used to construct the vector sequences in the epsilon-algorithm table. Two numerical examples are given to demonstrate the applications of the proposed method. The comparisons of the proposed method, the full analysis of the Newmark method and the Kirsch method are given in the first numerical example.